2018
DOI: 10.3390/s18041004
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Muscle Activation Models for Elbow Motion Estimation

Abstract: Adoption of wearable assistive technologies relies heavily on improvement of existing control system models. Knowing which models to use and how to improve them is difficult to determine due to the number of proposed solutions with relatively little broad comparisons. One type of these models, muscle activation models, describes the nonlinear relationship between neural inputs and mechanical activation of the muscle. Many muscle activation models can be found in the literature, but no comparison is available t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
25
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 35 publications
(98 reference statements)
0
25
0
Order By: Relevance
“…Actuation of tension within the muscle-tendon complex is realized from integration of active and passive elements. Hill-type models of muscle tension generally comprise an active contractile element and passive elastic elements arranged serially and in parallel [1,2,3]. Moreover, the mechanical behavior of the muscle-tendon complex is typically categorized into one of four principal actions: concentric, isometric, eccentric, and reactive [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Actuation of tension within the muscle-tendon complex is realized from integration of active and passive elements. Hill-type models of muscle tension generally comprise an active contractile element and passive elastic elements arranged serially and in parallel [1,2,3]. Moreover, the mechanical behavior of the muscle-tendon complex is typically categorized into one of four principal actions: concentric, isometric, eccentric, and reactive [4].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the mechanical behavior of the muscle-tendon complex is typically categorized into one of four principal actions: concentric, isometric, eccentric, and reactive [4]. Humans’ propensity for producing muscular strength and power during concentric, isometric, and eccentric actions is effectually described by the force-length and force-velocity dependencies of active and passive muscle-tendon elements [1,2,3]. Modelling the reactive capacity or strength of the muscle-tendon complex is more contemporary and has attracted considerable attention in recent literature.…”
Section: Introductionmentioning
confidence: 99%
“…As a non-invasive technique, surface EMG is widely applied, but it is also subject to numerous factors in the measuring and processing of EMG data that can compromise the outcome [ 26 , 27 , 28 , 29 , 30 ]. The post-processed and normalised EMG signal represents a time-dependent input parameter for muscle-activation dynamics that introduce a delay between the muscle’s electrical and mechanical onset, and non-linear relation between the EMG and the generated muscle force [ 31 , 32 ]. With the activation known, a Hill-type phenomenological model [ 33 ] is commonly used for the contraction dynamics to simulate the force generated by the muscle-tendon units.…”
Section: Introductionmentioning
confidence: 99%
“…Tsai et al [16] carried out a comparison of upper-limb motion pattern recognition while using multichannel EMG signals from the shoulder and elbow during dynamic and isometric muscle contractions. Suberbiola et al [17] captured the biceps and triceps EMG signals and found more precise movement with the use of algorithms that are based on autoregressive models and artificial neural networks Recently, Desplenter and Trejos [18] have evaluated seven muscle activation models by means of an EMG-driven elbow motion model. Many differences were found between models suggesting that further evaluation and improvements of motion models is still necessary in order to increase the safety and feasibility of the wearable assistive devices.…”
Section: Introductionmentioning
confidence: 99%
“…The calculation of the variable L CE is achieved by means of Equations (13)-(16): (16) Once defined the muscle model, it is necessary to describe the dynamics of the arm by means of the Equation 17, as shown in Figure A5. The momentum of inertia J arm is obtained with the Equation (18) in order to achieve the arm dynamics.…”
mentioning
confidence: 99%